Positioning of the dispersive electrode and its effect on the safety and efficacy of radiofrequency ablation - Berjano, Enrique (2024)
We recently read the article entitled “Impact of dispersive patch electrode positioning on safety and efficacy of radiofrequency catheter ablation” by Futyma, Zarębski and Sauer. The authors state that the position of the patch has an impact in terms of RF lesion size. Specifically, they state that: “When the dispersive patches are placed incorrectly, it can lead to suboptimal lesion formation and potentially increase the risk of adverse events.” However, they do not provide any reference to this, and in fact there is not currently enough clinical evidence in the literature to allow such a statement.In our previous studies based on computational modeling, we did not observe asignificant clinical impact of the different positions of the dispersive electrode on lesion size. In the article by Futyma et al, the authors cite our two previous works and emphasize some of the limitations of our methodology in order to cast doubt on our findings. However, contrary to what the authors claim, 1) cardiac lesion depths were really calculated considering the impact on extracardiac structures (lung, connective, bonny structures, etc.), and 2) the conductivity and resistivity of lungs were taken from a well recognized database, which is exactly the same as the one used by other authors of a recent modeling work whose conclusion is apparently in line with what Futyma et al claim. It seems that for the authors in silico modeling is an appropriate toolonly when the results agree with their point of view.Other limitations mentioned by the authors, such as 1) the impact of cumulative thermal injury of the oesophagus from multiple sequential and overlapping RF applications, 2) the fluctuations in oesophageal resistivity which can lead to higher current density in the oesophageal region, and 3) the fact that atrio-oesophageal fistula formation is multifactorial, available in silico models may not provide a definitive estimation of RF current pathways in view of DPE positioning, simply have very little to do with the impact of DPE positioning on lesion size.The authors conclude that the position of dispersive patch during RF catheter ablation is a critical factor that affects safe and effective lesion formation. Our conclusion after reading the article is that, as stated in the journal section, this is simply their point of view, and that there is not enough scientific evidence to show that repositioning the DPE in general allows modulating the size of the RF lesion.